Adolescent Substance Use and the Brain: Behavioral, Cognitive and Neuroimaging Correlates - Hamidullah, Shahnaza; Thorpe, Hayley H. A.; Frie, Jude A.; Mccurdy, Richard D.; Khokhar, Jibran Y. (Frontiers in Human Neuroscience, 2020)
Adolescence is an important ontogenetic period that is characterized by behaviors such as enhanced novelty-seeking, impulsivity, and reward preference, which can give rise to an increased risk for substance use. While substance use rates in adolescence are generally on a decline, the current rates combined with emerging trends, such as increases in e-cigarette use, remain a significant public health concern. In this review, we focus on the neurobiological divergences associated with adolescent substance use, derived from cross-sectional, retrospective, and longitudinal studies, and highlight how use of these substances during adolescence may relate to behavioral outcomes. Identifying and understanding the associations between adolescent substance use and changes in cognition, mental health, and future substance use risk may assist our understanding of the consequences of drug exposure during this critical window.